Strategies for delivering drugs across the blood-brain barrier for the treatment of neurodegenerative diseases - Zhang, Xiaopei; Fu, Manfei; Wang, Yuanfei; Wu, Tong (Frontiers in Drug Delivery, 2025)
The blood-brain barrier (BBB) restricts development of drug delivery systems for brain, which hinders the potential applications of numerous pharmaceutical agents for treating central nervous system (CNS) diseases. A number of drug delivery systems have been developed to enhance the capacity of drugs to cross BBB. A detailed introduction of the structure and function of BBB was given based on the mechanism of BBB, while comparing with the pathological changes of BBB in neurodegenerative diseases (NDDs), including activation of endothelial cells, the loose of tight junction and increase of BBB permeability. The liposomes, polymer nanoparticles and other novelty approaches for treating NDDs were summarized. Here, we provide a novel perspective to classify the strategies of drug delivery system as passive targeting and active targeting according to their mechanisms. The potential of clinical translational for drug delivery systems in NDDs was explored and underscored the imperative of safety and verification through clinical trials. In summary, this review proposed current developments of drug delivery systems and discussing the potentials of drug delivery systems in clinical translational which bring new breakthroughs for treating NDDs.